2004
DOI: 10.1111/j.1464-410x.2004.04604.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of caveolin‐1 and microvessel density correlates with metastasis and poor prognosis in clear cell renal cell carcinoma

Abstract: RESULTSEighteen patients had either synchronous or metachronous metastases and 11 died during the follow-up. Caveolin-1 intensity was significantly correlated with tumour size ( P = 0.005), TNM stage ( P = 0.028), M stage ( P = 0.012), grade ( P = 0.015), and metastasis (synchronous or metachronous; P < 0.001). The caveolin-1 proportion ( P = 0.037) and MVD ( P = 0.011) were significantly correlated with metastasis. MVD was correlated with caveolin-1 intensity ( r = 0.385, P = 0.001) and caveolin-1 proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 29 publications
8
104
1
2
Order By: Relevance
“…Support for this notion is in part provided by other clinical studies that show that the overexpression of caveolin-1 is correlated with increased microvessel density within tumours not only of the kidney (Joo et al, 2004) but also the prostate (Yang et al, 2007). Therefore, we present a hypothetical model (adapted from Li et al, 2003) for the coordinated role of caveolin-1 and the AKT/mTOR pathway in RCC disease progression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Support for this notion is in part provided by other clinical studies that show that the overexpression of caveolin-1 is correlated with increased microvessel density within tumours not only of the kidney (Joo et al, 2004) but also the prostate (Yang et al, 2007). Therefore, we present a hypothetical model (adapted from Li et al, 2003) for the coordinated role of caveolin-1 and the AKT/mTOR pathway in RCC disease progression.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequently, several laboratories have independently examined the expression of caveolin-1 (Horiguchi et al, 2004;Joo et al, 2004;Phuoc et al, 2007) or activated AKT/ mTOR/S6 (Lin et al, 2006;Pantuck et al, 2007;Robb et al, 2007) in RCC. However, none has yet examined the expression of these pathways together.…”
mentioning
confidence: 99%
“…Caveolin 1 has been demonstrated to have a suppressing and promoting role in pancreatic cancer, lung cancer, esophageal squamous cell carcinoma, renal cell carcinoma, prostate cancer and melanoma (6)(7)(8)(12)(13)(14). Previous studies have found that patients with a high caveolin 1 expression have more progressive diseases, and caveolin 1 has been demonstrated to have tumor promoting and pro-survival functions in more advanced disease stages (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…However, caveolin 1 has also been demonstrated to have a tumor promoting role in prostate cancer, renal cancer and esophageal squamous cell carcinoma (6)(7)(8), suggesting that whether caveolin 1 acts as tumor suppressor or facilitator depends upon specific tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…18 Caveolin expression, shown to be a marker of unfavorable prognosis, seems to be associated with a higher vascular density as well. 17 …”
Section: Angiogenesismentioning
confidence: 99%